Desinterés de los padres de familia en las tareas escolares de sus representados en el Sub Nivel Elemental, Periodo 2016-2017 - Farinango Guamani, Carmen del Rocio (2017)
The family is the first link in society and therefore the parents must fulfill shared responsibilities with their children, and be part of the education of their represented, the problem lies in the lack of parents´ participation in their children´s school homework, the children of the fourth year "A" at “Naciones Unidas” elementary school do not accomplish their school homework efficiently and sometimes they do not do them, that is why, most parents have limited economic resources and do work activities outside and inside home with different schedules, which does not allow them to share enough time with their children, it is very essential that parents take the responsibility to check their children´s homework in an efficient way and get involved, giving them the necessary support in the formal education, since this helps to strengthen the family bond creating trust, security and self-esteem in children. Therefore, this research aimed to inform parents about the importance of their involvement in their children´s school life, by mean of the quantitative methodology was used through the use of surveys and interviews where the results generated a 70 % in the parents´s participation in their children school homework. This research project to its term generated a practical contribution that consists in contributing with important data on how parents´ role is affecting the school homework, that allowed developing strategies in which parents can control the school homework, which achieved a social impact that focused on children´s performance and therefore the beneficiaries were children, parents, managers and teachers.